A Speech Act Analysis Of Direct Utterances On Short Story Mr. Know All - Mudzakir, Ahmad, Drs. Sigit Haryanto, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This research is aimed at (1) identifying the form of the direct sentences on short story entitled Mr. Know All, (2) describing the purposes of the direct utterances in short story entitled Mr. Know All, (3) show the kinds of speech act on direct utterances in short story Mr. Know All. The object used to be analyzed are direct utterances of short story Mr. Know All. In collecting the data, the writer uses documentation method by selecting the direct utterances which can be found in short story Mr. Know All. Having analyzed the data, the writer find that (1) the form of direct sentences are divided into three; declarative sentence, interrogative sentences and imperative sentences; (2) related to the purpose of utterances, the writer finds that the purposes of utterances depends on the four factors; locution, illocution, perlocution and situational context; (3) related to the kinds of speech act, the writer finds 7 kinds of speech act, they are assertive utterances, performative utterances, verdictive utterances, expressive utterances, directive utterances, commisive utterances, and phatic utterances.